RESHAPE THE LOGISTICS STRATEGY IN E-COMMERCE (CASE STUDY: SHOPEE AND LAZADA) - Glenn Evorius Pattiata; Jelita Sparta; Liem Gai Sin (AIBPM Publisher, 2018)
E-commerce has been playing the biggest role of furthest reaches of the economy business. E-commerce, in the popular sense, is a business transaction such as selling electronic network or internet. But we can all agree that, logistic take a crucial part of e-commerce. The objectives of this paper is to define which logistic strategy should have used in e-commerce in Indonesia (Shopee and Lazada). A differentiation of logistic strategy based on service enhancement can offer competitive advantage. Keywords: e-commerce, logistic strategy